Hemodynamic Evaluation of Nonselective β-Blockers in Patients with Cirrhosis and Refractory Ascites. (9th May 2018) - Ferrarese, Alberto; Tikhonoff, Valerie; Casiglia, Edoardo; Angeli, Paolo; Fasolato, Silvano; Faggian, Diego; Zanetto, Alberto; Germani, Giacomo; Russo, Francesco Paolo; Burra, Patrizia; Senzolo, Marco
Abstract : Background . Nonselective β -blockers (NSBB) have been associated with increased incidence of paracentesis-induced circulatory dysfunction (PICD) and reduced survival in patients with cirrhosis and refractory ascites. Aim . To prospectively evaluate a hemodynamic response to NSBB in cirrhotics listed for liver transplantation with refractory ascites undergoing large volume paracentesis (LVP). Methods . Patients with cirrhosis and refractory ascites, with an indication to start NSBB in primary prophylaxis for variceal bleeding, were enrolled. During two consecutive LVP, while being, respectively, off and on NSBB, cardiac output (CO), systemic vascular resistances (SVR), peripheral vascular resistances (PVR), and plasma renin activity (PRA) were noninvasively assessed. Results . Seventeen patients were enrolled, and 10 completed the study. Before NSBB introduction, SVR (1896 to 1348 dyn·s·cm −5 ; p = 0.028 ) and PVR (47 to 30 mmHg·min·dl·ml −1 ; p = 0.04 ) significantly decreased after LVP, while CO showed an increasing trend (3.9 to 4.5 l/m; p = 0.06 ). After NSBB introduction, LVP was not associated with a significant increase in CO (3.4 to 3.8 l/m; p = 0.13 ) nor with a significant decrease in SVR (2002 versus 1798 dyn·s·cm −5 ; p = 0.1 ). Incidence of PICD was not increased after NSBB introduction. Conclusion . The negative inotropic effect of NSBB was counterbalanced by a smaller decrease of vascular resistances after LVP, probably due to splanchnic β 2-blockade. This pilot study showed that NSBB introduction may be void of detrimental hemodynamic effects after LVP in cirrhotics with refractory ascites.